Maternal health and characteristics of mothers in selected barangays of Tigbauan, Iloilo. - Orquejo, Ildefonso M., Jr
This study aims to find out if maternal health status of mothers varies with their characteristics. specifically, it aims to find out if maternal health status varies with their economic status, educational attainment, and level of utilization of maternal health care services. The study uses a census of all mothers who gave birth last 2005 in certain barangays of Tigbauan, Iloilo. For th analysis, the researchers make use of the frequency and percentage distribution method. The study shows that the mothers with low economic status are unhealthy. However, its rate does not have significant gap with mothers who gave high economic status but are still unhealthy. thus, the researchers conclude that maternal health status of mothers does not vary with their economic status. The same conclusion is true for maternal health and educational attainment of mothers. The study found out that majority of mothers who have low educational attainment are unhealthy, while still majority of mothers who have high educational attainment are also unhealthy. Lastly, the researchers draw entirely the same conclusion with maternal health and the level of utilization of maternal health care services. Maternal health status of mothers does not vary with their level of utilization of maternal health care services because the study reveals that whether maternal health care services are completely utilized or underutilized, still majority of the mothers are unhealthy. The researchers, thus, recommend that in conducting pararllel research study of maternal health, additional variables like the number of children that the mother already has before the study was conducted, as well as the history of the mother's health. Investigating their health history will give one a complete understanding about maternal health.